Optimizing the Treatment of Atopic Dermatitis in Infants Using Ursodeoxycholic Acid - O.H. Shadrin; H.A. Haiduchyk (Zaslavsky O.Yu., 2016)
Expediency of including the suspension of ursodeoxycholic acid into the combination therapy of atopic dermatitis in infants was investigated. It is proved that administration of the suspension of ursodeoxycholic acid in 25 infants with atopic results has caused a positive clinical dynamics of both dermic and gastrointestinal symptoms that manifested by a reduction in the area of skin lesion, intensity of itching, normalization of dream and regression of pain abdominal syndrome, vomiting.